Additions to the Flora of Rajaji National Park, Uttarakhand (India) - Deroliya, P.K.; Kumar, Puneet; Singh, S.K.; Ghosh, Poulami (Indian Forester, 2024)
The main objective of this compilation is to offer a comprehensive understanding of the 25 additional angiosperm species that have been found in Rajaji National Park. To ensure accurate identification, synonym(s) associated with each species are provided. The compilation also includes a brief description of the key characteristics of each species and information on their phenology, which refers to the timing and patterns of their life cycle events. Additionally, specific details about the specimens that were examined during the study are documented. This comprehensive approach aims to provide a thorough understanding of these angiosperm species and facilitate further research and exploration in Rajaji National Park.